RANCANG BANGUN PLTMH SKALA KECIL DENGAN SISTEM ON-GRID UNTUK RESPONS DINAMIS TERHADAP PERUBAHAN BEBAN LISTRIK - Larobu, Feliks Eldad; Erdani, Yuliadi; Badia, Bahdin Ahad; Rachim, La Ode Muhamad Fathur (Jurnal Multidisipliner Kapalamada, 2025)
This research aims to design and develop a small-scale micro-hydro power plant that is directly connected to the electrical grid (on-grid system). The system is specifically engineered to respond quickly to changes in power demand, thereby helping to maintain the stability of the electrical network. The micro-hydro power plant utilizes water resources by harnessing river flow to generate clean and renewable electrical energy. The study focuses on evaluating the technical design, system performance, and response time to power fluctuations. Results from the experimental testing indicate that an increase in the rotational speed of the turbine shaft leads to a corresponding increase in electrical output. Furthermore, the testing location plays a significant role in the system’s efficiency. The first location demonstrated superior turbine performance, producing an output of 27.52 Watts, while the second location yielded a significantly lower power output of only 5.68 Watts. This research offers an efficient and sustainable solution for small-scale electricity generation.